Poziom produkcji roślinnej w Polsce na tle wybranych państw Unii Europejskiej - Klepacki, Bogdan; Jakóbik, Anna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2004)
In the paper the level of plant production in Poland in comparison with leading EU countries was presented. There were showed areas of some plants in Denmark, France, Nederland and Germany as well as received yields of cereals, potatoes, sugar beets and rapes compared with scored in Poland in 2002. It was stated that received yields were in Poland 25 to 38% lower than in European Union.